Original paperAnalysis of skin patch test results and metalloproteinase-2 levels in a patient with contact dermatitis - Wojciechowska, Milena; Czajkowski, Rafał; Kowaliszyn, Bogna; Żbikowska-Gotz, Magdalena; Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction: The complex course of skin reactions that contact eczema involves is due in part to abnormalities of the extracellular matrix function. Proteins that degrade extracellular matrix components include metalloproteinases (MMP), which are divided into subcategories depending on the chemical structure and substrate specificity. Aim : To analyse patch test results in contact dermatitis patients and to assess MMP-2 levels during skin lesion exacerbation and remission. Material and methods : Fifty patients suffering from contact eczema were qualified to the study and 20 healthy volunteers as a control group. The study group patients had epidermal skin tests performed with the “European Standard” set. To assess the MMP-2 level in serum, venous blood was drawn, twice from study group patients – during contact dermatitis exacerbation and remission periods – and once from control group patients. Assessment of MMP-2 in serum was done with ELISA immunoassay. To verify the proposed hypotheses, parametric and nonparametric significance tests were used. Results : Hands were the most frequent location of contact dermatitis. Nickel (II) sulphate was the most frequent sensitizing substance. Mean MMP-2 levels were statistically higher in the study group both in contact dermatitis exacerbation and remission periods than in the control group. There was no statistically significant difference between MMP-2 levels and skin patch test results. Conclusions : Nickel is one of the most allergenic contact allergens in patients with contact dermatitis. Metalloproteinase-2 is a good marker of contact dermatitis in various stages of the disease.